South Africa : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses South Africa's recent growth performance and its new growth targets. It analyzes the history of exchange rate volatility, compares it with other countries, and examines the relationship between volatility and trade flows in South Africa. It highlights facts on reserves holding and presents an empirical analysis of a model in assessing the adequacy of South Africa's reserves. It also analyzes the cyclical balances to determine revenue performance and discusses the penetration of the South African financial conglomerates into State Security Agency and assesses potential vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet